Malcolm Turnbull — A Feisty Interview with the Shadow Minister - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2020)
Liz Fell’s interview in 2011 with the Australian Shadow Minister for Telecommunications, Malcolm Turnbull MP, was notable for his combativeness (rare amongst her interviewees). In tribute to both Ms Fell and Mr Turnbull, we republish that interview with the future Prime Minister who, as Minister for Communications in 2013-15, implemented the multi-technology mix redesign of the National Broadband Network.